CSC099: Foundation Computing II / Centre of Foundation Studies - UiTM, Centre of Foundation Studies (Universiti Teknologi MARA (UiTM), 2022)
This course introduces basic computer programming algorithm, problem solving, structured programming language, selection structure, repetition structure, function and array. It is specially designed for foundation engineering students according to basic requirements for most bachelor degree in engineering programs and industries. The purpose of this course is to equip students with abilities to construct algorithms in problem solving, to create computer systems as well as having high level of logical and critical thinking skills that are required for their future studies. The aims of this course will be achieved through small scale lecture class and extensive lab exercises starting with basic programming structure to challenging programming problems. In addition, a high quality of academic exercises such as individual assignment and group project will be used to achieve these aims. By the end of this course, students are expected to acquire and apply knowledge of computer programming to respective fields of engineering, computer science and business.